On‐Chip Screening of a Glycomimetic Library with C‐Type Lectins Reveals Structural Features Responsible for Preferential Binding of Dectin‐2 over DC‐SIGN/R and Langerin. Issue 54 (3rd September 2018) - Medve, Laura; Achilli, Silvia; Serna, Sonia; Zuccotto, Fabio; Varga, Norbert; Thépaut, Michel; Civera, Monica; Vivès, Corinne; Fieschi, Franck; Reichardt, Niels; Bernardi, Anna
Abstract: A library of mannose‐ and fucose‐based glycomimetics was synthesized and screened in a microarray format against a set of C‐type lectin receptors (CLRs) that included DC‐SIGN, DC‐SIGNR, langerin, and dectin‐2. Glycomimetic ligands able to interact with dectin‐2 were identified for the first time. Comparative analysis of binding profiles allowed their selectivity against other CLRs to be probed. Abstract : A library of mannose‐ and fucose‐based glycomimetics was synthesized and screened in a microarray format against a set of C‐type lectin receptors (CLRs) that included DC‐SIGN, DC‐SIGNR, langerin, and dectin‐2. Glycomimetic ligands able to interact with dectin‐2 were identified for the first time.